Simulate the natural four-season fermentation system for high-salt diluted-state soy sauce brewing: Application in flavor promotion regulation - Changzheng Wu; Hui Wu; Xiya Yu; Tianchang Jia; Tao He; Qinhui Hong; Xing Tong (PLoS ONE, 2025)
The seasonal temperature dependency of soy sauce fermentation poses significant challenges to flavor consistency, particularly under low-temperature conditions (e.g., 15°C in winter), where diminished aroma arises from microbial metabolic constraints. Traditional multi-year field studies to decipher these mechanisms are impractical for rapid industrial optimization. In this study, we present an innovative laboratory-based seasonal temperature simulation fermentation system that precisely replicates climatic conditions (15–37°C) of the Lingnan region, enabling accelerated investigation of microbial dynamics and targeted strain interventions. Our findings revealed that, compared to the 30°C (simulating the autumn season) fermented soy sauce, which exhibits optimal flavor, 15°C (simulating the winter season) had a weaker flavor of soy sauce due to the low relative abundance of specific strains, especially Staphylococcus lloydii, Leuconostoc lactis, and Kodamaea ohmeri. Those three strains were added into the low-temperature fermentation process, Staphylococcus lloydii and Kodamaea ohmeri promoted the formation of soy sauce key aroma compounds, such as benzene acetaldehyde, 1-octen-3-ol, and ethyl acetate. Our research offers the soy sauce industry a feasible tool to efficiently and cost-effectively test the reinoculation of functional microbial strains, thereby ensuring consistent flavor profiles throughout the year.